The origin of autoimmune diseases: is there a role for ancestral HLA-II haplotypes in immune hyperactivity - Ruiz-Pablos, Manuel; Paiva, Bruno; Zabaleta, Aintzane (Frontiers in Immunology, 2025)
The prevalence of autoimmune diseases in contemporary human populations poses a challenge for both medicine and evolutionary biology. This review explores how the ancestral human leukocyte antigen class II (HLA-II) haplotypes DR2-DQ6, DR4-DQ8 and DR3-DQ2 could play a central role in susceptibility to these diseases. We propose that these haplotypes, selected in historical contexts of high infectious pressure, may have been maintained because of their ability to elicit strong T-cell responses against pathogens; however, that antigenic promiscuity may be associated with an increased tendency toward immune hyperreactivity in modern environments. This hyperreactivity, involving proinflammatory cytokines including interferon-gamma (IFN-γ), could contribute to the breakdown of tolerance and the emergence of autoimmunity and related clinical phenomena (e.g., Long COVID, myalgic encephalomyelitis/chronic fatigue syndrome and post-vaccination syndromes), although the evidence for the latter remains limited. Finally, we discuss how chronic infections, immunotherapies, vaccination, obesity and chronic physical stressors may exacerbate this susceptibility and consider the therapeutic implications of integrating HLA-II profiling into clinical practice.